2021
DOI: 10.1111/ijd.15464
|View full text |Cite
|
Sign up to set email alerts
|

Oral mini‐pulse therapy in vitiligo: a systematic review

Abstract: Background There is limited evidence supporting the use of alternative treatments for patients with nonstable vitiligo.Objective This study aimed to review the effects of oral mini-pulse (OMP) therapy in the management of nonsegmental vitiligo. MethodsThe following databases were searched between inception and May 2020 for relevant studies: Scopus, Web of Science, MEDLINE, and Embase. All randomized controlled trials that compared OMP therapy with any other active treatment or placebo for nonstable vitiligo we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
(109 reference statements)
0
6
0
Order By: Relevance
“…52 A recent systematic review examining studies on oral mini pulse in vitiligo found a high risk of bias and a low quality of evidence in the available literature. 53 The authors could not muster enough sound evidence to echo the claims of efficacy of OMP therapy in arresting disease progression and re-pigmentation in patients with nonstable vitiligo.…”
Section: A Better Option Is To Use An Intermediate-acting Steroid Adm...mentioning
confidence: 99%
See 1 more Smart Citation
“…52 A recent systematic review examining studies on oral mini pulse in vitiligo found a high risk of bias and a low quality of evidence in the available literature. 53 The authors could not muster enough sound evidence to echo the claims of efficacy of OMP therapy in arresting disease progression and re-pigmentation in patients with nonstable vitiligo.…”
Section: A Better Option Is To Use An Intermediate-acting Steroid Adm...mentioning
confidence: 99%
“…NB‐UVB and methylprednisolone 0.5 mg/kg on 2 consecutive days per week for at least 3 months has been found to produce a greater than 25% re‐pigmentation in 59.4% patients and was found to arrest disease progression in all patients 52 . A recent systematic review examining studies on oral mini pulse in vitiligo found a high risk of bias and a low quality of evidence in the available literature 53 . The authors could not muster enough sound evidence to echo the claims of efficacy of OMP therapy in arresting disease progression and re‐pigmentation in patients with nonstable vitiligo.…”
Section: Principle and Practise Of Rationale Dosimetrymentioning
confidence: 99%
“…We read with interest the article by Chavez‐Alvarez et al. entitled “Oral mini‐pulse therapy in vitiligo: a systematic review.” 1 Oral mini‐pulse therapy, pioneered by Pasricha and Khaitan in the management of vitiligo, aims primarily at stopping the progression of the disease 2 . We noticed that as per the method of this review only four studies were included, and therefore some of the important non‐RCT studies could not be included in this review.…”
Section: Figurementioning
confidence: 99%
“…Dexamethasone has been frequently used in oral administration due to its low mineralocorticoid action. Oral pulse therapy (OPT) has been commonly used in dermatology for alopecia areata, vitiligo, and alopecia Universalis, among others, with good results [ 2 , 3 ]; in neurology, it has been used to treat chronic inflammatory demyelinating polyneuropathy [ 4 ]. An exciting work by Luetic et al [ 5 ], from Argentina, that, in times of Covid, with the impossibility of performing conventional pulse therapy, OPT has been used to treat multiple sclerosis with good efficacy.…”
mentioning
confidence: 99%